A novel HPLC method for the determination of zonisamide in human plasma using microextraction by packed sorbent optimised by experimental design. Issue 40 (12th October 2017) - Lourenço, Dina; Sarraguça, Mafalda; Alves, Gilberto; Coutinho, Paula; Araujo, André R. T. S.; Rodrigues, Márcio
Abstract : A novel high-performance liquid chromatography-diode array detection method based on microextraction by packed sorbent as a sample preparation approach was developed and validated for the determination of zonisamide in human plasma. Abstract : A novel high-performance liquid chromatography-diode array detection method based on microextraction by packed sorbent (MEPS) as a sample preparation approach is described for the determination of zonisamide (ZNS) in human plasma. MEPS parameters were optimised using a Plackett–Burman experimental design to achieve the best extraction conditions. The chromatographic separation of ZNS and chloramphenicol [internal standard (IS)] was achieved in less than 5 min on a C18-column, at 35 °C, using a mobile phase composed of acetonitrile/water (35 : 65, v/v) pumped isocratically at 1.0 mL min −1 . ZNS and IS were detected at 240 nm. No endogenous and exogenous interference was observed at the retention times of the analyte of interest (ZNS) and IS. A good linearity was obtained for ZNS ( r 2 = 0.9960) in the range of 0.2–80 μg mL −1 in plasma. The method was shown to be precise (CV ≤ 13.3%) and accurate (bias ±12.3%), and the absolute recovery ranged from 63.8% to 65.2%. The stability of ZNS was demonstrated in plasma samples under all predictable handling and storage conditions. The proposed assay was applied to the analysis of human plasma samples obtained from epilepsy patients under ZNS therapy, and the results supported its usefulness for therapeutic drug monitoring in clinical practice.